Environmental Management in Aquaculture: A Review of Good Aquaculture Practice from Sustainability Perspectives - Pebryeni, Resti (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The rapid development of aquaculture plays an important role in supplying fish protein, but it also generates various environmental problems. Objective: This article aims to examine the role of Good Aquaculture Practice (GAP) in supporting sustainable environmental management in aquaculture. Methods: This study employed a literature review with a content analysis approach on 15 national and international scientific articles published between 2020 and 2025. Results and Discussion: The review indicates that GAP implementation mainly focuses on water quality and waste management, with pond-based aquaculture being the most frequently studied system. Studies on technology-based and integrated aquaculture systems remain relatively limited. Conclusion: Good Aquaculture Practice represents an important framework for sustainable environmental management in aquaculture; however, a more integrated approach is required to strengthen its future implementation